The Role of Village Banks In Reducing Poverty In Sengguruh Village, Kepanjen District, Malang Regency - Jose Rizal Joesoef; Hertoto Dwiyoso; Sulistiyanti; Adinda Dwi Putri (International Journal of Economics and Business Management, 2025)
This study aims to describe the role of Village Banks in reducing poverty and increasing community income in Sengguruh Village, Kepanjen District, Malang Regency. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation of Village Bank customers and managers. The results indicate that Village Banks facilitate access to business financing, encourage increased income, and foster more independent financial behavior. Convenient services, low interest rates, and a family-like approach make Village Banks a more humane financing alternative compared to informal institutions. Despite facing limited capital and low financial literacy, Village Banks continue to play a strategic role in empowering the rural economy.